Influence of ethical behavior on Corporate Governance of firm’s performance in Ghana. (International Journal of Scientific Research and Management (IJSRM), 2018)
This study aims at analyzing the influence which ethical behavior has on the corporate governance of firm’s performance in Ghana. The existing of ethical issues in business organizations and the general code of conduct which these companies are supposed to follow has brought about the need for researchers to assess their implications to the management of these firms. The findings in this study are essential in acknowledging the impact of ethical behavior on the management of the organization. This study has given us an in-depth understanding of the effects of ethical attributes such as ethical leadership and corporate governance to the overall financial development and performance of firms in Ghana